Relation of the Mandibular Canal to the Root Apices of Different Types of Impacted Lower 3rd Molar - Shahrazad S Saad; Asmaa B Al -Saffar; Bara S Minwah (University of Mosul, College of Dentistry, 2012)
Aims: The study aims to determine the radiographic relationship of the inferior dental canal to the roots of impacted lower third molars. Materials and Methods: Sixty one patients were examined radio graphically by using conventional orthopantomograph (OPG) for detecting the relationship of the root apices of different types of impacted lower third molars to the inferior dental canal. Results: The sam-ple enrolled included 61 patients (30 males and 31 females) with a total of 100 impacted lower third molars. Age of patients included in the study ranged from 17 to 48 years within an average age of (32.5 %). Bilateral impaction was noticed in 39 patients (63.9 %), whereas unilateral impaction was observed in 22 patients (36.1 %). The greater number of impacted lower 3rd molar were of mesioangular angula-tions and were accounted in 40 impacted teeth (40 %) of the sample ,followed by vertical impaction 29 %, and horizontal impaction 23 %, while the inverted and distoangular angulations represented 4 % each. Seventy three roots (38 mesial and 35 distal roots) were categorized as "adjacent" relationship and 63 roots (32 mesial and 31 distal roots) categorized as "notching" and 53 roots (26 mesial and 27 distal roots) were categorized as "super imposition" with only one root ,mesial root categorized as "grooving". The remaining 10 roots (3 mesial and 7 distal roots) could not be placed under any of these categories. Therefore, they were placed in the category X or none. Conclusion: Within the limitations of this study, the mesioangular impaction is the most problematic type of impaction and "adjacent" relationship of mandibular third molar to inferior dental canal is most common type.